Molecular Umbrellas: a Novel Class of Candidate Topical Microbicides To Prevent Human Immunodeficiency Virus and Herpes Simplex Virus Infections - Madan, Rebecca Pellett (American Society for Microbiology, 2007)
Molecular umbrella compounds may function as novel topical microbicides to prevent human immunodeficiency virus (HIV) and herpes simplex virus (HSV) infections. In a preliminary structure-activity investigation, one umbrella compound, designated Spm8CHAS, was identified which inhibited both HIV and HSV infections with no cellular toxicity. The objectives of the current studies were to define its spectrum of antiviral activity, characterize its mechanism of action, and explore the possibility of combining Spm8CHAS with HIV-specific reverse transcriptase inhibitors. Spm8CHAS inhibited infections by laboratory and clinical R5 and X4 clade B and clade C HIV strains in cell culture. Ectocervical tissue explants exposed to HIV-1(BaL) in the presence of Spm8CHAS were completely protected (50% inhibitory concentration [IC(50)], 13.6 μg/ml), and transfer of virus to target T cells via migratory cells was abolished (IC(50), 3.8 μg/ml). Spm8CHAS inhibited HSV-2 infection of epithelial cells 10,000-fold if present throughout the infection. Notably, adding Spm8CHAS to cultures following HSV entry significantly reduced viral infection, indicating that the drug also acts postentry. Subsequent studies indicated that Spm8CHAS blocks cell-to-cell spread of HSV. Confocal microscopy using a fluorescently labeled analog of Spm8CHAS demonstrated that this conjugate crosses the plasma cell membrane and is transported to the nucleus. Combinations of Spm8CHAS with UC-781 or 9-[R-2-(phosphonylmethoxy)propyl] adenine monohydrate in vitro exhibited additive anti-HIV activity with preserved anti-HSV activity. The abilities of Spm8CHAS to inhibit primary isolates of HIV, block HSV infection postentry, and cross cell membranes support the development of a combination microbicide containing Spm8CHAS with an HIV-specific reverse transcriptase inhibitor to prevent both HIV and HSV infections by multiple mechanisms.